Fibrous Dysplasia Of Maxilla: A Case Report - Ayub, Kinza; Rizwan, Zarnab; Rizwan, Ghina; Bibi, Haleema; Fazal, Mohsin (Journal of Rawalpindi Medical College, 2023)
Summary: Fibrous dysplasia is a benign disease of unclear aetiology that is congenital and recurring in nature. It is caused by a problem known as bone modelling, in which the normal bone constantly changes and is replaced by immature fibrous tissue. One or more bones may be impacted by the lesion; the maxilla is the most often afflicted facial bone. Expansile lesions known as fibrous dysplasia lead to issues related to the original location. The most often involved region in the craniofacial bone is the maxilla. In this case report 50 years 50-year-old female patient reported who has maxillary fibrous dysplasia. Keywords: fibrous dysplasia, congenital, bone.